Production shocks, exports and market prices: An analysis of the rice sector in Myanmar - Dorosh, Paul A.; Win, Myat Thida; van Asselt, Joanna (International Food Policy Research Institute, 2019)
Since 2012/13, rice exports to China (which may have reached two million tons in 2015/16) boosted total demand for Myanmar’s rice and rice prices. In mid-2016, however, China stopped rice imports through the main land entry point, putting substantial downward pressure on prices. Analysis presented in this paper, based on econometric estimates of consumption parameters and a simple model of Myanmar’s rice supply and demand, suggests that market prices would fall by 26 to 43 percent or more (in real terms) in the absence of increased exports to the world market and/or government domestic procurement. Such a decline in prices could have seriously harmed Myanmar’s rice producers, including many poor farmers with marketable surpluses. Model simulations suggest that government procurement of about one million tons would limit the estimated price decline to only 17 to 30 percent. Further refinements in the simulations are needed to take account for the seasonal nature of paddy production in Myanmar, possible price-responsiveness of export demand and the effects of changes in paddy incomes on farmer demand for rice. Medium-term analysis of procurement, storage and future sales is needed to analyze fiscal costs under various scenarios, as well, covering alternative shocks to production, export demand and world prices. Nonetheless, the main results are clear: without substantial market interventions on the order of one million tons (milled rice equivalent), the paddy (rice) price could fall dramatically when production increases or export demand declines.